The Effect of Content Marketing on Purchase Intention With E-Wom as A Mediation Variable on Hanasui Products in Tiktok Shop (Case Study On Generation Z) - Windarti Ardy Putri Ardy (Universitas Negeri Surabaya, 2025)
This study was conducted to evaluate the extent to which Content Marketing influences Purchase Intention, with Electronic Word-of-Mouth (E-WOM) as a mediating variable, for Hanasui products on the TikTok Shop platform. Data collection was carried out through the distribution of an online questionnaire targeting Generation Z, particularly those who actively use TikTok. This study employs a quantitative approach using Structural Equation Modeling (SEM) analysis. The results indicate that Content Marketing significantly influences consumer purchase intention, and E-WOM strengthens this relationship as a mediating variable. These findings provide strategic implications for local brands like Hanasui to further optimize their digital marketing efforts through TikTok Shop in order to attract the purchasing interest of Generation Z.